Uji Aktivitas Antioksidan Ekstrak dan Fraksi Buah Jambu Biji Australia (Psidium Guajava L.) Metode DPPH - Marshela Duta Larasati; Desy Ayu Irma Permatasari; Isna Nur Khasanah (Journal of Educational Innovation and Public Health, 2023)
Australian guava fruit (Psidium guajava L.) is thought to have antioxidant activity. Antioxidants are compounds that are useful for treating oxidative damage caused by free radicals in the body. The aim of this study was to determine the secondary metabolite content and IC50 value on the antioxidant activity of extracts and fractions from Australian guava fruit. This research used four solvents, including 70% ethanol extract, n-hexane fraction, ethyl acetate fraction and water fraction with varying concentrations of 50 ppm, 100 ppm, 150 ppm, 200 ppm and 250 ppm. The antioxidant test was carried out using a UV-Vis spectrophotometry tool with the DPPH method at a wavelength of 515 nm with an incubation time of 15 minutes. Antioxidant activity tests show that Australian guava fruit is effective as an antioxidant in capturing free radicals. The IC50 value for the ethanol extract is 0.784 µg/mL, the n-hexane fraction is 2.448 µg/mL, the ethyl acetate fraction is 1.015 µg/mL and the water fraction is 0.676 µg/mL. All samples were included in the very strong category, but the water fraction had the best antioxidant activity among the ethanol extract, n-hexane and ethyl acetate fractions.